Two channels of metal-rich compact stellar system formation: starbursts under high ram pressure versus tidal stripping - Bian, Yuan; Du, Min; Debattista, Victor P.; Nelson, Dylan; Norris, Mark A.; Ho, Luis C.; Lu, Shuai; Cen, Renyue; Ma, Shuo; Ge, Chong; Fang, Taotao; Li, Hui (The astrophysical journal. Part 2, Letters, 2025)
Most galaxies follow a well-defined scaling relation between metallicity and stellar mass; however, some outliers at the low-mass end of the observed galaxy population exhibit unusually high metallicity for their mass. Understanding how these objects get to be so metal-rich is vital for understanding the role of feedback in galaxy formation. Using the TNG50 simulation, we explore the origins of this phenomenon. We identify 227 metal-rich, compact stellar systems (CSSs) that deviate significantly from this scaling relation. These CSSs are satellites located in the vicinity of massive host galaxies, with stellar masses ranging from 108 to 1010 M⊙ (including six systems that are close analogs of the M31-M32 system). Contrary to the previously assumed scenario that such objects are predominantly products of tidal stripping, we find that more often ram pressure plays a major role in their formation. Indeed, 76% (173) of these CSSs are formed through a burst of star formation occurring around the time of the first pericentric passage, typically at redshifts z ≲ 1, aided by strong ram pressure and tidal forces. The high ram pressure, resulting from the CSSs’ rapid motion near the host halo center, facilitates metal enrichment, producing high-metallicity CSSs by confining the metal-rich gas from bursty star formation, which leads to distinct stellar populations characterized by enhanced metallicity and high α-abundance. The other 24% (54) of metal-rich CSSs are generated through the tidal stripping of massive progenitors. Our results further indicate that M32 is more likely to have formed through intense star formation events rather than through gradual tidal stripping.
Gesehen am 24.09.2025